Association Between ACL Continuity on Magnetic Resonance Imaging at 5 Years After an Acute ACL Rupture and 11-Year Outcomes : A Secondary Analysis From the KANON Trial - Filbay, Stephanie R.; Roemer, Frank; Roos, Ewa M.; Turkiewicz, Aleksandra; Frobell, Richard; Lohmander, L. Stefan ; 0000-0002-5424-9448; Englund, Martin ; 0000-0003-3320-2437 (American Journal of Sports Medicine, 2025)
Background: Emerging evidence suggests that anterior cruciate ligament (ACL) ruptures can restore ACL fiber continuity. The relationship between ACL continuity on magnetic resonance imaging (MRI) (sign of ACL healing) and outcomes >5 years after an acute ACL rupture has not been investigated. Purpose: This study aimed to (1) describe clinical outcomes and radiographic osteoarthritis (ROA) at 11 years based on ACL continuity status at 5 years and (2) investigate the relationship between 5-year ACL continuity status and 11-year Knee Injury and Osteoarthritis Outcome Score (KOOS4) scores. Study Design: Secondary analysis of KANON randomized controlled trial; Level of evidence, 3. Methods: Overall, 105 of 121 (87%) active adults with acute ACL ruptures randomized to undergo initial exercise therapy and optional delayed ACL reconstruction (ACLR) or early ACLR and postoperative exercise therapy completed 11-year follow-up. MRI scans at 5 years were evaluated using the Anterior Cruciate Ligament OsteoArthritis Score (0-3), with grades 0 to 2 considered to represent “ACL continuity.” Patient-reported outcomes (KOOS4, 36-Item Short Form Health Survey, Tegner Activity Scale, self-reported new knee injuries), knee laxity, and radiographic findings (tibiofemoral and/or patellofemoral ROA) were assessed at 11 years. The relationship between 5-year ACL continuity and 11-year KOOS4 scores (0-100) was examined using linear regression, adjusted for age, sex, smoking, and baseline KOOS4 scores. Results: Of patients managed nonsurgically, 58% (n = 14) had ACL continuity and 42% (n = 10) had ACL discontinuity at 5 years. Analyses suggest that ACL continuity was associated with worse 11-year KOOS4 scores compared with delayed ACLR (adjusted mean difference, –20.2 [95% CI, –31.9 to −8.6]) and early ACLR (adjusted mean difference, –15.5 [95% CI, –26.4 to −4.7]) as well as similar or worse KOOS4 scores compared with ACL discontinuity (adjusted mean difference, –11.4 [95% CI, –26.5 to 3.6]). The proportion of patients with tibiofemoral ROA ranged from 14% (ACL continuity) to 23% (delayed ACLR), and the proportion of patients with patellofemoral ROA ranged from 11% (ACL discontinuity) to 41% (early ACLR). Conclusion: ACL continuity on 5-year MRI may be associated with worse patient-reported outcomes at 11 years after an ACL injury compared with early or delayed ACLR.
Keywords: anterior cruciate ligament reconstruction; magnetic resonance imaging; osteoarthritis; rehabilitation